Overview of waste in lowland santista and its use in renewable energy generation (Research, Society and Development, 2021)
This studs aims to present an overview of the situation of garbage in the Santos region, as well as its generation, treatment and destination, as well as to present how its use can be beneficial in the generation of non-renewable energy, not only for the energy issue but mainly as a solution for the destination of the generated urban waste.  Exploratory descriptive research. In view of the existing problems with garbage in the RMBS, some alternatives for the use of garbage as renewable energy are suggested, such as the resumption of the ELBAS Project and the example of the DELTA Landfill, in addition to the installation of companies that concentrate the organic waste produced by municipalities in a centralized manner, not only reduces the areas of deposition, but also transforms the cost of destination into remuneration for needy communities in these regions. Despite the management of urban waste in these municipalities complying with the legislation, their costs and environmental risks involved until their proper destination, not only burden their economies but raise criticisms about the environmental risks involved. The resumption of projects for the collection of biogas, together with the implementation of actions that value waste, generate a reduction in socio-environmental and financial impacts for the cities of the Lowland Santista Metropolitan Region.